Venous access in neonates: our experience - Sharma, Pramod Kumar; Singh, Santosh Kumar (International Journal of Contemporary Pediatrics, 2018)
Background: The aim of this work was to study various tools for intravenous access in neonates, both short- and long-term, and their feasibility and associated complications. Methods: Records of 366 neonates who required three or more days of hospital admission were retrieved and included in the study. Their requirements of intravenous fluids, and medications and parenteral nutrition were recorded. The type of intravenous (IV) device, its in-situ duration, any complications and the frequency of need to change it were recorded. Results: 42 patients needed long-term (more than 7 days) indwelling cannula and central line insertion. The indications were prolonged stay with the need for IV fluids, need for prolonged antibiotics, and parenteral nutrition. Commonest complication was local thrombophlebitis. Other complications noted were fever and local skin necrosis. Conclusions: Neonatal care has come a long way in last few decades and involves high-end NICUs, advanced ventilators, and other similar gadgets and methodologies. This applies to both, medical as well as surgical neonates. This mandates prolonged admission and various invasive procedures, including surgical operations. Obtaining a secure and long-term venous access automatically becomes an important part of this kind of neonatal care. There are now available a plethora of intravenous cannulas and devices for various indications of intravenous access in neonates. The present article discusses the experience of various options available for intravenous access in neonates including their complications and prevention of the latter.